Influence of celebrity endorsement on the buying behavior of Nepal - Upadhyay, Jitendra Prasad; Niroula, Ballav (NCC Journal, 2022)
The main objective of this research is to find out the influence of the celebrity endorsement on buying behavior of people in Nepal. A descriptive research design has been used for the analysis of available information. Four independent variables (Attractiveness, Celebrity, Expertise, and Trust Worthiness) and a dependent variable ‘Buying behavior’ are considered in this study. Structured questionnaires were distributed to the respondent for the collection of information. Responses from the 205 respondents have been used for the analysis. Questionnaires were distributed using the convenience sampling technique. Inferential statistics have been applied to interpret and analyze the data. Data are explained and analyzed using Excel and SPSS software. The result found that celebrity endorsement affects the buying behavior of people. The marketplace must carefully assess the celebrities to ensure that the target clients have a favorable perception of them.